Effect of surface treatments on shear bond strength of denture teeth to denture base resins - Farideh Bahrani; Amir Ali Reza Khaledi (Wolters Kluwer Medknow Publications, 2014)
Background: Debonding of denture teeth from denture bases is the most common failure in removable dentures. The purpose of this study was to evaluate the effect of surface treatments on shear bond strength of denture teeth to heat-polymerized and autopolymerized denture base resins. Materials and Methods: In this experimental in vitro study, 60 maxillary central incisor acrylic teeth were divided into two groups. Group M was polymerized with heat-polymerized acrylic resin (Meliodent) by compression molding technique and group F was processed by autopolymerized acrylic resin (Futura Gen) by injection molding technique. Within each group, specimens were divided into three subgroups according to the teeth surface treatments (n = 10): (1) ground surface as the control group (M 1 and F 1 ), (2) ground surface combined with monomer application (M 2 and F 2 ), and (3) airborne particle abrasion by 50 μm Al 2 O 3 (M 3 and F 3 ). The shear bond strengths of the specimens were tested by universal testing machine with crosshead speed of 5 mm/min. Data were analyzed by two-way analysis of variance (ANOVA) and Tukey's honestly significant difference (HSD) tests (P < 0.05). Results: The mean shear bond strengths of the studied groups were 96.40 ± 14.01, 124.70 ± 15.64, and 118 ± 16.38 N for M 1 , M 2 , and M 3 and 87.90 ± 13.48, 117 ± 13.88, and 109.70 ± 13.78 N for F 1 , F 2 , and F 3 , respectively. The surface treatment of the denture teeth significantly affected their shear bond strengths to the both the denture base resins (P < 0.001). However, there were no significant differences between the groups treated by monomer or airborne particle abrasion (P = 0.29). The highest percentage of failure mode was mixed in Meliodent and adhesive in Futura Gen. Conclusion: Monomer application and airborne particle abrasion of the ridge lap area of the denture teeth improved their shear bond strengths to the denture base resins regardless of the type of polymerization.